RESPONS PEMBERIAN BERBAGAI PUPUK MAJEMUK DAN MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Solanum lycopersicum) VARIETAS PERMATA SECARA HIDROPONIK - Andi Apriany Fatmawaty; Imas Rohmawati; Fenny Nahariah Marianie (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2016)
This research was aimed to know the response of various compound manure and growing media to growth and yield of tomato (Solanum lycopersicum) Permata variety as hydrophonics. The research was conducted at Caringin Village, Labuan Sub-District from November 2013 until February 2014. The research used Randomized Completely Block Design which consisted of two factors. The first factor was various compound manure, which consisted of three levels; P1 = Gandapan; P2 = Gandasil D; and P3 = Gandasil B. The second factor was growing media, which consisted of three levels: M1 = husk charcoal; M2 = Malang sand; and M3 = husk charcoal : Malang sand 1:1. The each treatment was repeated three times, so there were 27 experimental units. The result showed that manure of Gandapan gave the best effect to parameters: the plant height 2 and 4-7 weeks after planting (54.74 cm), the number of leaves 2, 7 and 8 weeks after planting (34.85 leaves), the number of fruits on 2, 4, 5 and 6 harvest time (5,67 fruits), the weight of fruits per plant (160,64 g), the weight of fruits per plant (154.81 g), the dry weight of plants (10.38 g), and and the length of roots (49.74 cm). The husk charcoal growing media gave the best effect on parameters of the plant height 2, 6-8 weeks after planting (53.22 cm), the number of fruits on 2nd harvest time (3,26 fruits), the weight of fruits per plant (154.95 g), fresh weight of plants (154.44 g), the dry weight of plants (10,11 g), and the length of roots (47.07 cm). There’s no interaction between combination of Gandapan and husk charcoal growing media, except on the dry weight of plant parameter (12.72 g).Keywords: Tomato, Compound manure, Hydrophonics